?SYNTHESIS OF HETERO-BICYCLIC COMPOUNDS PART-X. FORMATION OF 2H,4H,5H 2,2-DIPHENYL-4, 5-DIOXOPYRIDO [4, 3-d] 1,3 DIOXIN (Biological Sciences - PJSIR, 2003)
Aminopyranodioxin derived from benzophenone isomerize to yield 6 substituted 1, 2-dihydropyridodioxins (III),whose structures were determined by chemical conversions and spectroscopic studies.